Beyond Reproduction: The "First 1,000 Days" Approach to Nutrition through a Gendered Rights-Based Lens - Mai-Lei Woo Kinshella; Sophie E. Moore; Rajavel Elango (Harvard FXB Center for Health and Human Rights, 2020)
The First 1,000 Days approach highlights the importance of adequate nutrition in early life-from conception to a child's second birthday-for good development and growth throughout the child's life and potentially onto their own offspring. The approach has been highly influential in mobilizing policy attention and resources to improve maternal and infant nutrition in global health and development. This paper undertakes a critical review of this approach from a gendered human rights lens, finding that the theoretical underpinnings implicitly reflect and reproduce gender biases by conceptualizing women within a limited scope of reproduction and child care. We explore the processes of systemic neglect through Pierre Bourdieu's theories on how social structures are reproduced. Understanding theory is important to the governance of global health, how we frame priorities, and how we act on them. Revisiting influential theories is a means of accountability to ensure inclusiveness and to reduce gender and health inequities in research. We argue that a greater focus on women could increase the potential impact of nutrition interventions.